Peran Ustadz dalam Membimbing Mental Santri Membentuk Kepribadian Islam di Pondok Pesantren an-Najah Kudus - Ahmad Ainun Najib (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
This study aims to determine the implementation of ustadz's mental guidance to students, to know the personality of Islamic students, to know the role of Ustadz in guiding students' mentality to shape Islamic personality. The ustadz has a very important role in guiding santri to become Islamic. The method used is qualitative. Data collection uses interviews, observation, documentation. The research informants were religious teacher and students. The results showed that the guidance of the Islamic teacher to students was held every week precisely on Monday after 19.15, Islamic Personality of students at An-Najah Islamic Boarding School Tanjungrejo Jekulo Kudus was very good, it was seen from students always following positive activities in their daily lives. The role of the Ustadz in guiding mentally Shaping the Islamic personality of the santri in An-Najah Tanjungrejo Islamic Boarding School Jacuro Kudus is done well, which is to provide encouragement and guidance so that students can apply the mau'idzha hasanah material in their daily lives.